Propuesta para la obtención de fibra textil a base de cáscara de naranja (2023)
This document presents a way to obtain textile fiber from orange peel waste. This proposal is made due to the search for environmentally friendly alternatives in the face of the current situation of pollution from the textile sector at the national level. and worldwide making use of organic waste that is not reused and on the contrary is discarded in the soil causing its deterioration, for this reason the use of orange peel discarded by small and large industries that use oranges for beverages, in addition, the peel of this fruit contains in its composition an appreciable content of fiber indicated to be able to produce textile fiber from it. The two most common types of orange in Colombia were taken, Valencia type orange and Tangelo type orange, a physicochemical characterization was carried out on each type of peel (percentage of humidity, ash, fat and fiber), in order to compare them. The results obtained showed that the Valencia type orange has more moisture and fiber content (67.8% and 9.6% respectively) compared to the tangelo type orange (56.2% and 8.7% respectively), while that the latter showed a higher content of ash and fat (4.8% and 3.3%) compared to the Valencia type orange (0.9% and 1.6%).